Avaliação da eficácia do Tribunal de Contas do Estado na implantação e funcionamento do Sistema de Controle Interno dos municípios mato-grossenses - Cunha, Isaías Lopes da (2021)
The Internal Control System provided for in arts. 31, 70 and 74 of the Constitution of the Republic, Federative of Brazil, regulated by federal, state and municipal laws, is called internal control. This system is responsible for the efficiency and effectiveness of the controls over the activities of public bodies, helping to prevent and detect the occurrence of errors, fraud and misuse of public resources. The general objective of the research is to evaluate the effectiveness of the actions of the Court of Auditors of the State in the implantation and functioning of the Internal Control System of the Mato Grosso municipalities in the perception of the servers of the internal control units. Data collection was carried out through survey research, using a structured questionnaire with closed questions on the profiles of respondents and internal control units and on the evaluation of the Court's actions, which was applied to a group of 93 servants of the internal control units of Mato Grosso's municipalities, with a population of 179 servants. The results showed that the actions of the State Court of Auditors obtained 88.62% effectiveness in the implementation and operation of the Control System of Mato Grosso's municipalities in the perception of employees of the internal control units. The research helps to show that the Courts of Auditors can be effective instruments in improving public administration